1991
DOI: 10.1007/978-3-642-84301-3_8
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Cooperative Cell Assemblies in the Visual Cortex

Abstract: SummaryDuring a critical period of postnatal development of the mammalian visual cortex, synaptic connections are susceptible to use-dependent modifications. Synaptic connections strengthen if pre-and postsynaptic elements are active simultaneously and postsynaptic depolarization is sufficient to allow for the activation of A'-methyl-D-aspartate (NMDA)-receptor-gated conductances. By contrast, synaptic gain decreases if postsynaptic activation exceeds a critical threshold and presynaptic afferents are not capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 63 publications
(56 reference statements)
0
37
0
1
Order By: Relevance
“…4). The formation of such assemblies has been related to system function by a number of researchers studying other systems (Singer, 1990;Abeles et al, 1993;Vaadia et al, 1995;Stopfer et al, 1997;Nicolelis et al, 1998;Laurent, 1999;Christensen et al, 2000). Although it is difficult to ascertain whether interactions between neurons provide "more" codingrelevant information than single-neuron firing patterns (as they seem to in olfaction), elimination of this information via random time shifting of individual responses significantly degraded the ability of the ensembles to discriminate between applied tastants (Fig.…”
Section: Gustatory Processing Via Coherent Rate Changes In Taste-specmentioning
confidence: 99%
“…4). The formation of such assemblies has been related to system function by a number of researchers studying other systems (Singer, 1990;Abeles et al, 1993;Vaadia et al, 1995;Stopfer et al, 1997;Nicolelis et al, 1998;Laurent, 1999;Christensen et al, 2000). Although it is difficult to ascertain whether interactions between neurons provide "more" codingrelevant information than single-neuron firing patterns (as they seem to in olfaction), elimination of this information via random time shifting of individual responses significantly degraded the ability of the ensembles to discriminate between applied tastants (Fig.…”
Section: Gustatory Processing Via Coherent Rate Changes In Taste-specmentioning
confidence: 99%
“…A correspondência retínica dos dois olhos é similar com relação à orientação, tamanho e resposta à velocidade ou à direção de movimento. Via de regra, o estímulo que vem de um olho predomina e produz resposta neuronal maior (31)(32)(33) . Não foi encontrada nenhuma análise relacionada à dominância ocular e relaxante limbar na literatura.…”
Section: Discussionunclassified
“…Experience-dependent modifications of cortical circuitries are not determined solely by local correlations of electrical activity but are also influenced by attentional mechanisms (Singer 1995). Sensory signals, for instance, promote marked modifications of neural circuitries only when animals attend to the sensory input and use this information for the control of behaviour (Singer 1990(Singer , 1995. Early studies performed in cats demonstrated that changes of visual cortical circuitries in response to experience during early life, are lessened when noradrenergic Bear & Singer 1986), cholinergic (Gu & Singer 1993) and serotonergic (Gu & Singer 1995;Wang et al, 1997) projections to the cortex are inactivated.…”
Section: Long-distance Projection Systems Regulate Plasticity In the mentioning
confidence: 99%